Strategi Pelayanan Ibadah Haji dalam Meningkatkan Kepuasan Jama'ah di Kementerian Agama Kabupaten Lebak - Nurasiah, Siti; Maesaroh, Imas (e-Jurnal Aksioma Al-Musaqoh : Journal of Islamic Economics and Business Studies, 2024)
Service strategy is important in an institution, especially those engaged in services, for example the Office of the Ministry of Religion of Lebak Regency is one of the institutions whose role is so great in helping to provide services to the community to be able to fulfill the fifth pillar of Islam, namely the Hajj. Important services provided by the Office of the Ministry of Religion of Lebak Regency to prospective pilgrims are services such as registration, guidance on Hajj rituals, services during the implementation of the Hajj pilgrimage and others. Considering the majority of prospective Indonesian pilgrims are parents, the best and maximum service needs to be done to provide comfort and satisfaction of prospective pilgrims. This research aims to find out and examine how the Ministry of Religious Affairs of Lebak Regency's Hajj service strategy in increasing congregation satisfaction. The method used in this research is a qualitative method that produces descriptive data using data collection techniques in the form of observation, in-depth interviews with the parties concerned and books that support the completeness of the data. The results of this study indicate that the hajj pilgrimage service strategy of the Ministry of Religious Affairs of Lebak Regency in increasing pilgrims' satisfaction has been carried out optimally and as well as possible.